2022
DOI: 10.5009/gnl210062
|View full text |Cite
|
Sign up to set email alerts
|

Continued Postoperative Use of Tumor Necrosis Factor-α Inhibitors for the Prevention of Crohn’s Disease Recurrence

Abstract: Background/Aims: Many patients with Crohn's disease (CD) undergo intestinal resection during the disease course. Despite surgery, postoperative recurrence (POR) commonly occurs. Although postoperative use of tumor necrosis factor α (TNF-α) inhibitors is known to be effective in preventing POR, few studies have evaluated the effectiveness of continuing the same TNF-α inhibitors postoperatively in patients who received TNF-ɑ inhibitors before surgery.Methods: This retrospective observational study was performed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 40 publications
(62 reference statements)
0
2
0
Order By: Relevance
“…In the study by Beelen et al, the advantage of anti-TNF agents as compared with thiopurines was observed not only in low- but also in high-risk patients, i.e., in those previously exposed to anti-TNF agents [ 110 ]. Finally, Yu et al [ 70 ] reviewed patients who had undergone the first intestinal resection due to CD and divided them into two groups: TNF inhibitor users in both the preoperative and postoperative periods, and TNF inhibitor users only in the preoperative period; the rates of surgical and endoscopic POR were not different between either group.…”
Section: Anti-tnf Agentsmentioning
confidence: 99%
“…In the study by Beelen et al, the advantage of anti-TNF agents as compared with thiopurines was observed not only in low- but also in high-risk patients, i.e., in those previously exposed to anti-TNF agents [ 110 ]. Finally, Yu et al [ 70 ] reviewed patients who had undergone the first intestinal resection due to CD and divided them into two groups: TNF inhibitor users in both the preoperative and postoperative periods, and TNF inhibitor users only in the preoperative period; the rates of surgical and endoscopic POR were not different between either group.…”
Section: Anti-tnf Agentsmentioning
confidence: 99%
“…Empirical medical treatments such as 5-aminosalicylic acids (5-ASA), immunomodulators or corticosteroids have been used to manage intestinal BD [ 5 , 6 ]. However, for patients who are refractory about medical treatments, surgery can be inevitable but preventing and managing postoperative recurrence represents another important field of research in IBD [ 7 10 ]. A few biologic agents have been successfully used to delay the progression of intestinal BD and treat refractory cases [ 2 4 , 11 15 ].…”
Section: Introductionmentioning
confidence: 99%